2012
DOI: 10.1517/14656566.2013.758713
|View full text |Cite
|
Sign up to set email alerts
|

Second-line treatments for the management of advanced renal cell carcinoma: systematic review and meta-analysis

Abstract: Results from the present study suggest that axitinib will be an important treatment option to extend PFS in the management of advanced RCC in the second-line setting. Ongoing research will define the optimal treatment algorithm leading to a patient-focused treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The results of our meta-analysis also indicated that axitinib exhibits a higher efficacy and safety compared to sorafenib and pazopanib in patients who previously received systematic treatment. This finding is also in line with a recent systematic review and meta-analysis for second-line treatments in the management of advanced RCC (28). The authors of that study reported that axitinib was superior to placebo (HR=0.25, 95% CI: 0.17-0.38) or sorafenib (HR= 0.46, 95% CI: 0.32-0.68) and pazapanib (HR= 0.47, 95% CI: 0.26-0.85) in prolonging PFS.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our meta-analysis also indicated that axitinib exhibits a higher efficacy and safety compared to sorafenib and pazopanib in patients who previously received systematic treatment. This finding is also in line with a recent systematic review and meta-analysis for second-line treatments in the management of advanced RCC (28). The authors of that study reported that axitinib was superior to placebo (HR=0.25, 95% CI: 0.17-0.38) or sorafenib (HR= 0.46, 95% CI: 0.32-0.68) and pazapanib (HR= 0.47, 95% CI: 0.26-0.85) in prolonging PFS.…”
Section: Discussionsupporting
confidence: 91%
“…These have been used as first-line therapy for renal cell carcinoma (RCC) and hepatocellular carcinoma worldwide and have demonstrated favorable outcomes. Recently, axitinib and pazopanib have been included as drugs that function as multikinase inhibitors; hence, multikinase inhibitors play an important role in cancer chemotherapy [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Note that, in Europe, temsirolimus is approved only ''for the first-line treatment of adult patients with advanced renal cell carcinoma (RCC) who have at least three of six prognostic risk factors'' 19 . While multiple second-line treatment options are available for mRCC, evidence for the comparative efficacy of these agents is limited 7,9,11,[20][21][22][23][24][25] . Due to the rapid emergence of multiple targeted agents within the past 8 years, comparative data from clinical trials is limited (and may never occur due to the cost of such trials).…”
Section: Introductionmentioning
confidence: 99%